From The Greek Commonwealth to The Commonwealth of Nations: Zimmern, Curtis, and a tale of two titles - Rood, T (Routledge, 2024)
This article analyses the development of the notion of ‘commonwealth’ within the Round Table group in relation to two books: Alfred Zimmern’s The Greek Commonwealth (1911) and Lionel Curtis’ The Commonwealth of Nations (1916). Modern historians of International Relations have argued that the title of Zimmern’s book alluded to conceptions of the British empire as a ‘commonwealth’. Drawing on previously unused archival sources and on detailed study of the different editions of The Greek Commonwealth, this article shows that Zimmern’s title did not refer to any form of political organization larger than the city-state and that IR historians have wrongly read into Zimmern’s book both the idea of commonwealth and the reading of the Athenian empire developed by Lionel Curtis. The article explores Curtis’ development of the concept of commonwealth and its reception by Zimmern and other members of the Round Table, and sets the historical narrative Curtis offers in The Commonwealth of Nations against The Greek Commonwealth. It shows that, even though Curtis used Zimmern’s work as a source, he took issue with its presentation of Athens precisely in relation to the questions of imperial organization that were the Round Table’s central concern.